Alfabetização científica : o ensino da leitura e escrita em uma escola estadual de tempo integral em Manaus/AM - Castro, Valdeni Liborio de (2016)
Scientific literacy emerges in the educational context with the development of science, based on the assumption provide conditions for effective participation of people in their reality. The theme scholars seek to show the need for the construction of this the early years through an education that allows the manipulation of students with elements for reading the world around him. In this context, this master thesis titled scientific literacy in the teaching of reading and writing in full-time State School of Santa Terezinha that has the general objective to analyze the teaching of reading and writing the scientific literacy process and seek through the theoretical contributions Soares ( 2010), Kleiman (1995), Tfouni (2010); Chassot (2003, 2011) Sasseron (2008), Lorenzetti Delizoicov (2001), Lemke (2006) among others, reflect the construction of scientific literacy for teaching reasoning processes and learning of reading and writing. To seek to achieve the goal pretedindo made a methodological approach is a qualitative research that is characterized by the direct contact of the researcher with suejitos surveyed to analyze the interrelations that are built in a given reality. The research took place at a public school in the city of Manaus with a 5th class of elementary school and the subjects were the teacher and the students in this class, and the school pedagogue. The data collection instruments were participant observation, interview and completion of three (3) activities with the students of the 5th year of the initial years. The results showed a reading of teaching design and writing that goes against the concept of literacy and the pedagogical practice of the researched teaching is geared to work with genres based on a dialogical perspective. In this context, we highlight the scientific literacy indicators developed for the teaching of reading and writing process that enables thus affirm the scientific literacy process is process in the research group. Keywords: reading design and writing; teaching practice; scientific literacy indicators.